Influence of the coronavirus 2 (SARS-Cov-2) pandemic on acute appendicitis - M. Velayos; A.J. Muñoz-Serrano; K. Estefanía-Fernández; M.C. Sarmiento Caldas; L. Moratilla Lapeña; M. López-Santamaría; J.C. López-Gutiérrez (Elsevier, 2020)
Introduction: Acute appendicitis (AA) is the most common abdominal surgical emergency. No specific studies have been found that evaluate the impact of the coronavirus 2 (SARS-Cov-2) pandemic on AA and its surgical management. An analysis was made on the influence of this new pathology on the clinical course of AA. Material and methods: Retrospective observational study was conducted on patients operated on for AA from January to April 2020. They were classified according to the time of the appendectomy, before the declaration of the state of alarm (Pre-COVID-19), and after its declaration (Post-COVID-19) in Spain, one the most affected countries in the world. An evaluation was made of demographic variables, duration of symptoms, type of appendicitis, surgical time, hospital stay, and postoperative complications. Results: The study included 66 patients (41 Pre-COVID-19; 25 Post-COVID-19) with mean age of 10.7 ± 3 and 9.3 ± 3.1; P = .073, respectively. Fever was found in a higher number of post-COVID-19 patients (52 vs 19.5%; P = .013), as well as a higher CRP (72.7 ± 96.2 vs 31.3 ± 36.2 mg/dL; P = .042). This group presented with a higher proportion of complicated appendicitis when compared to Pre-COVID-19 (32 vs 7.3%; P = .015). The mean hospital stay was longer in the Post-COVID-19 group (5.6 ± 5.9 vs 3.2 ± 4.3 days; P = .041). No differences were found in the time of onset of symptoms or surgical time. Conclusions: The SARS-Cov-2 pandemic influenced the time of diagnosis of appendicitis, as well as its course, and mean hospital stay. Peritonitis was more frequently seen. As a result of the significant circumstances, delaying diagnosis and treatment of AA during SARS-Cov-2 pandemic, inappropriate management of this common surgical disorder has been noticed. Resumen: Introducción: La apendicitis aguda (AA) es la urgencia quirúrgica abdominal más frecuente. No encontramos estudios específicos que evalúen el impacto de la pandemia causada por el coronavirus 2 (SARS-Cov-2) sobre la AA y su tratamiento quirúrgico. Analizamos la influencia de esta nueva patología sobre la AA. Material y métodos: Estudio observacional retrospectivo en pacientes intervenidos por AA desde enero hasta abril de 2020. Fueron clasificados según el momento de la apendicectomía, antes de la declaración del estado de alarma (Pre-COVID19) y después de la declaración del estado de alarma (Post-COVID19) en España. Se evaluaron variables demográficas, duración de la sintomatología, tipo de apendicitis, tiempo quirúrgico, estancia hospitalaria y complicaciones postoperatorias. Resultados: Se incluyeron 66 pacientes (41 Pre-COVID19; 25 Post-COVID19 con edad media de 10.7 ± 3 y 9.3 ± 3.1; P = .073; respectivamente). La fiebre se encontró en un mayor número de pacientes post-COVID19 (52 vs 19.5%; P = .013), así como una PCR más elevada (72.7 ± 96.2 vs 31.3 ± 36.2 mg/dl; P = .042). Este grupo presentó una mayor proporción de apendicitis complicada al compararle con el Pre-COVID19 (32 vs 7.3%; P = .015). La estancia media hospitalaria fue mayor en el grupo Post-COVID19 (5.6 ± 5.9 vs 3.3 ± 4.3 días; P = .041). No se encontraron diferencias en el tiempo de evolución de los síntomas ni en el tiempo quirúrgico. Conclusiones: La pandemia por SARS-Cov-2 influye en el momento de diagnóstico de la apendicitis, así como en su grado de evolución y estancia hospitalaria. La peritonitis fue lo más frecuentemente observado. Una sospecha y orientación clínica más temprana, es necesaria para evitar un manejo inadecuado de este trastorno quirúrgico común.